Hydroconversion of asphaltene in a hydrogen donor solvent: Stability analysis of the asphaltene-solvent colloidal system. (1st May 2020) - Sheng, Qiang; Wang, Gang; Jin, Nan; Husein, Maen M.; Gao, Jinsen
Graphical abstract: Highlights: A new colloidal system was built by dissolving asphaltene in hydrogen donor. The stability of the built colloid was first time investigated. The stability was characterized by separability number, Δ G M, and onset of precipitation. The stability of the colloid reduced with reaction time. Increased aromaticity of the asphaltene leads to the colloid system unstable. Abstract: Asphaltene aggregation and precipitation out of the reaction mixture limits the extent of its hydroconversion. In this work, the colloidal stability of asphaltenes undergoing hydroconversion in tetralin solvent was monitored with time. The separability number was measured and the Gibbs energy of mixing together with the onset of asphaltene precipitation were calculated. The results show that the hydrogen transfer from tetralin to asphaltene radicals effectively quench the radicals. The colloidal stability of the system, nevertheless, decreased with reaction time and vanished for reaction times >3 h. In line with this observation, the onset of asphaltene precipitation decreased and, while the Gibbs energy of mixing was negative, it increased with time. The colloidal stability of the reaction system was chiefly influenced by the increased aromaticity of the asphaltene, which in turn decreased its solubility parameter. Within the stable colloidal domain, approximately 44% of the asphaltenes were converted with <1 wt% coke generation. This work is the first attempt in the literature to analytically and mathematically characterize the colloidal stability of asphaltenes undergoing reactions in a hydrogen donor solvent.